2016
DOI: 10.1128/mcb.00809-15
|View full text |Cite|
|
Sign up to set email alerts
|

UV Damage-Induced Phosphorylation of HBO1 Triggers CRL4DDB2-Mediated Degradation To Regulate Cell Proliferation

Abstract: e Histone acetyltransferase binding to ORC-1 (HBO1) is a critically important histone acetyltransferase for forming the prereplicative complex (pre-RC) at the replication origin. Pre-RC formation is completed by loading of the MCM2-7 heterohexameric complex, which functions as a helicase in DNA replication. HBO1 recruited to the replication origin by CDT1 acetylates histone H4 to relax the chromatin conformation and facilitates loading of the MCM complex onto replication origins. However, the acetylation statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 51 publications
2
34
0
Order By: Relevance
“…Although ubiquitylation of HBO1 by DDB2 leading to degradation appears from 2 h after ultraviolet irradiation15, HBO1 pS50/53 signals were detected on the chromatin at least 2 h after ultraviolet irradiation (Fig. 1b).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Although ubiquitylation of HBO1 by DDB2 leading to degradation appears from 2 h after ultraviolet irradiation15, HBO1 pS50/53 signals were detected on the chromatin at least 2 h after ultraviolet irradiation (Fig. 1b).…”
Section: Resultsmentioning
confidence: 97%
“…We previously reported that Ser50 and Ser53 of HBO1 were phosphorylated in response to various DNA damage treatments15. Based on these observations, we examined whether HBO1 is involved in survival against ionizing radiation (IR), which induces oxidative damage, single-strand breaks (SSBs) and some DSBs, or mitomycin C (MMC) treatment, which induces both inter- and intrastrand crosslinks.…”
Section: Resultsmentioning
confidence: 99%
“…) and KAT7/HBO1/MYST2 (Matsunuma et al . ), the histone deacetylases HDAC1/2 (Zhao et al . ; Zhu et al .…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] It was suggested that HBO1 can acetylate either H4 or H3K14 depending on the composition of the HBO1 protein complex partners. [21,22,[30][31][32] TIP60 can acetylate H2A-K5, H2A-K15, H3K14, H4K5, H4K8, H4K12, and H4K16 in cell-free assays, [33,34] but appears to be restricted to H2A-K5 in cells. [21,22,[30][31][32] TIP60 can acetylate H2A-K5, H2A-K15, H3K14, H4K5, H4K8, H4K12, and H4K16 in cell-free assays, [33,34] but appears to be restricted to H2A-K5 in cells.…”
Section: Broad or Histone Lysine Residue-specific Hat Activity?mentioning
confidence: 99%
“…In cells, shRNA KD shRNA depletion of HBO1 profound reduction in H3K14ac and H3K9ac, acetylation of H4K5 and 8 reduced to lesser degree [22] HBO1 H3K14 Genetic deletion, mouse cells Cells from Hbo1 null embryos, >90% reduction of H3K14ac, no reduction in acetylation of H4K5, 8, and 12, and upregulation of H4K16ac and H3K9ac [21] HBO1 H3K14 In cells, shRNA Depletion of HBO1 ablated H3K14ac in MLE cells [32] HBO1 H3K14 In cells, siRNA Depletion of HBO1 caused reduction in H3K14ac [30] HBO1 H3K14 Constitutive HBO1 HBO1 Ser50/53Ala mutant cells, deregulated H3K14ac [31] HBO1 H3K14 H4…”
Section: H3k9acmentioning
confidence: 99%